Construction and application of a precise evaluation method for the quality of traditional Chinese medicine based on “target-combined quality evaluation” using safflower as an example - Zhou, Yongfeng; Wu, Qinghua; Ren, Chaoxiang; Jiang, Huajuan; Huang, Xulong; Chen, Jiang; Zhang, Ping; Zhang, Dingkun; Pei, Jin (Frontiers in Pharmacology, 2025)
IntroductionThe quality of traditional Chinese medicine (TCM) guarantees clinical efficacy. At present, although chemical quality evaluation methods can reflect the quality of TCMs to a certain extent, there are still many problems. This study proposes a new strategy for the quality innovation evaluation of the TCM “target combined quality evaluation” (TCQE) theory and method. Taking the “disease-target-medicine” combination as the main fusion strategy, using drug components/ components to achieve the overall intervention of disease targets, and establishing the TCQE strategy of TCM to improve the pertinence and accuracy of the quality evaluation of TCM, the clinical efficacy and safety of TCM is improved, and precision clinical medication is achieved.MethodsTaking safflower as the research object, due to its main efficacy in the treatment of primary dysmenorrhea (PD), the potential targets and mechanism of action of safflower in the treatment of PD were analyzed by a network pharmacology method and combined with a metabolomics method. The pathway and mechanism of action of safflower in the treatment of PD were analyzed from multiple dimensions. The network pharmacology and metabolomics results were analyzed, the key targets of safflower in the treatment of PD were screened. Finally, a method for the biological evaluation of safflower quality was established based on the selected targets, which could provide a reference for the precise evaluation of safflower treatment and a scientific basis for the clinical application of safflower in the prevention and treatment of PD.Results and discussionThe pharmacodynamic results showed that Safflower significantly improved Prostaglandin E2 (PGE2) and Prostaglandin F2 α (PGF2 α) levels, the PGF2 α/PGE2 ratio and the analgesic rate in PD rats. The results of network pharmacology combined with metabolomics analysis showed that Prostaglandin G/H synthase 2 (PTGS2) and arachidonic acid (AA)were important targets and pathways of Safflower in the treatment of PD. A biological evaluation method was established around PTGS2. The results of the methodological investigation showed that the method was stable and reliable. In vivo validation experiments showed that the results of this method were consistent with the pharmacodynamic results, which proved its accuracy. PTGS2 is an important target of safflower in the treatment of PD. The biological evaluation method established around PTGS2 can accurately evaluate the quality of Safflower in the treatment of PD, which also proves that the target discrimination theory proposed in this study is scientific.